Religious Education Between Radicalism and Tolerance (Wiener Beiträge zur Islamforschung,, 2018)
The authors of this volume examine theory and practice regarding past and present roles of Jewish, Christian and Islamic religious education in nurturing tolerance, interpreted as mutual respect for and recognition of other groups, in Eastern (Albania, Bulgaria, Kosovo, Macedonia, Moldova, Montenegro and Romania) and Western (Finland, Germany, Italy, Latvia and Spain) Europe, Israel, Nigeria and Uzbekistan. They also explore potential roles of religion and exclusivism in fostering (Islamic state, NGOs, etc.), but also averting (Islamic legal theory, authority, Sufism, etc.) radicalization, and of secular states in allowing, but also banning minority religious education in public schools. With contributions from Friedrich Schweitzer, Martin Rothgangel, Gerhard Langer, Daniela Stan, Arto Kallioniemi, Juan Ferreiro Galguera, Maria Chiara Giorda, Rossana M. Salerno, Viorica Goraş-Postică, Constantin Iulian Damian, Valentin Ilie, Dzintra Iliško, Ayman Agbaria, Zilola Khalilova, Raid al-Daghistani, Osman Taştan, Moshe Ma'oz, Adriana Cupcea, Muhamed Ali, Rüdiger Lohlker and Dele Ashiru. The Editors Ednan Aslan is the Chair of Islamic Theological studies at the University of Vienna where he is a Professor for Islamic Education. Margaret Rausch is scholar, researcher and university instructor in the field of Islamic and Religious Studies.